Generic Model for Mobile Tourists Guide System (GMMTGS) - Elarbi, Mohamed B. SH. (2009)
Nowadays, information discovery becomes more relevant to peoples' lifestyle with the implementation of mobile technology. In different ways, people can gather information they need just about anywhere without having to be physically connected to the Internet. With the support of Wireless Application Protocol (WAP), the development of mobile application turns to be realistic and reliable as it follows the correct protocol. This study has developed and designed a generic mobile tourist system based on tourists' requirements. The study used the JSP language and MYSQL server for the system development. Furthermore, the proposed system was tested using use test case with five students. Finally, the proposed generic mobile tourists guide system aims to satisfy tourist needs.